ANALISIS KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA DHAHA KOTA KEDIRI - Antika, Rada Rindi; Sasongko, M. Zuhdi (Universitas Nusantara PGRI Kediri, 2022)
The purpose of this study was to analyze the quality of service to customer satisfaction of the Regional Water Company (PDAM) Tirta Dhaha, Kediri City. This study uses the dimensions of service quality, namely Tangibles, Reliability and Responsivness. This study uses a qualitative descriptive approach. Determination of informants in this study using purposive sampling technique, while the informants that the researchers determined were the head of the sub-section of complaints and PDAM customers. The results of this study indicate that PDAM Tirta Dhaha services still need to be improved, starting with facilities and infrastructure, the services provided are not wholehearted in serving customers and responsiveness in handling customer complaints. The findings of this study are that the services provided by PDAM Tirta Dhaha are not optimal. Recommendations from researchers in providing PDAM Tirta Dhaha services are by improving facilities and infrastructure, serving customers wholeheartedly and maximally, handling customer complaints quickly and on time and conveying information clearly